2009
DOI: 10.1186/1476-4598-8-111
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of TGF-β on ERα-mediated estrogenic transcriptional activity in breast cancer

Abstract: BackgroundTGF-β resistance often develops in breast cancer cells that in turn overproduce this cytokine to create a local immunosuppressive environment that fosters tumor growth and exacerbates the invasive and metastatic behavior of the tumor cells themselves. Smads-mediated cross-talk with the estrogen receptor has been implied to play an important role in development and/or progression of breast cancer. We investigated how TGF-β regulates ERα-induced gene transcription and potential mechanisms of frequent T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…In contrast to Smad2/3, the interaction with ERα does not lead to Smad4 degradation [234]. Overexpression of Smad3 or inhibition of Smad4 leads to a change of role of TGF-β from a repressor to an activator of the ERα signaling cascade [235]. On the other hand, Smad4 can induce apoptosis in an ERα-dependent manner in ERα-positive but not in ERα-negative breast cancer cells.…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%
“…In contrast to Smad2/3, the interaction with ERα does not lead to Smad4 degradation [234]. Overexpression of Smad3 or inhibition of Smad4 leads to a change of role of TGF-β from a repressor to an activator of the ERα signaling cascade [235]. On the other hand, Smad4 can induce apoptosis in an ERα-dependent manner in ERα-positive but not in ERα-negative breast cancer cells.…”
Section: Crosstalk With Tgf-β Signalingmentioning
confidence: 99%
“…Smad3-dependent transcription is inhibited by ER␣ through binding to Smad3, and the inhibition is abrogated by the expression of AP-1 transcription factors (33,34). A complex of Smad3/4 mediates the inhibition of ER␣-mediated estrogenic activity of gene transcription in breast cancer cells (35). In addition, ER␣ interacts with Smad1, which is a downstream signal transducer of BMP signaling, to inhibit BMP-induced transcription (36,37).…”
mentioning
confidence: 99%
“…R-SMAD3 has been found to be a co-activator of ERα changing the role of TGF-β. In the absence of Co-SMAD4, TGF-β can regulate ERα transcription through a R-SMAD3-mediated process and enhance the estrogen-ERα cell proliferation [131]. In fact, Araki and colleagues found that 65% of late stage breast cancers are characterized by activated R-SMAD3 and HDM2, a negative regulator of the tumor suppressor p53 [134].…”
Section: Crosstalk Between Tgf-β and Erα Signaling Pathwaysmentioning
confidence: 99%
“…Several studies have provided evidence that receptor regulated SMADs (R-SMAD2, R-SMAD3) and common mediator (Co-SMAD4) comes into direct physical contact with ERα [129][130][131][132]. Co-SMAD4 is found to be a mediator of crosstalk between TGF-β and ERα where it acts as a co-repressor of the transcription of ERα, inhibiting tumor growth.…”
Section: Biological Mechanism: Estrogen Links Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation